GE_GERICHTE C/5221/2011 vom 7. Februar 2013 - GE Cour de justice (2013)
DÉCISION INCIDENTE; HUISSIER; MANDAT; RESPONSABILITÉ DE L'ÉTAT; EXPULSION DE LOCATAIRE | CPC.237; aLOJ.45; aLPC.473; aLPC.474; aLPC.474A